A phase 1 study of prasugrel in patients with sickle cell disease: pharmacokinetics and effects on ex vivo platelet reactivity - Jakubowski, Joseph A.; Zhou, Chunmei; Small, David S.; Winters, Kenneth J.; Lachno, D. Richard; Frelinger, Andrew L.; Howard, Jo; Mant, Timothy G.; Jurcevic, Stipo; Payne, Christopher D. (British journal of clinical pharmacology, 2013)
Aims Prasugrel is a novel thienopyridine P2Y12 adenosine diphosphate (ADP) receptor antagonist that inhibits ADP‐mediated platelet activation and aggregation. Accordingly, it may be useful in reducing platelet‐related ischaemia in sickle cell disease (SCD). Exposure to prasugrel's active metabolite (Pras‐AM) and its antiplatelet activity in SCD have not been investigated. Methods Thirteen adult patients with SCD and an equal number of matched healthy control subjects were studied before and after 12 days of 5.0 or 7.5 mg day−1 prasugrel treatment. Platelet reactivity was assessed by light transmission aggregometry (LTA), impedance aggregometry (MEA), VerifyNow® P2Y12, vasodilator‐stimulated phosphoprotein (VASP) phosphorylation and Plateletworks. Exposure to Pras‐AM was also assessed. Results At baseline, patients with SCD showed increased platelet reactivity vs. healthy control subjects with VerifyNow (408 vs. 323 P2Y12 reaction units (PRU), respectively, P = 0.003) and MEA (106 vs. 77 area under the aggregation curve (AU.min), P = 0.002); lower platelet reactivity index with VASP flow cytometry (59 vs. 79% platelet reactivity index (PRI), P = 0.018); and no significant differences with LTA, VASP enzyme‐linked immunosorbent assay or Plateletworks. Relative to baseline, prasugrel significantly reduced platelet reactivity by all assays in both populations (all P < 0.05). Prasugrel was well tolerated, with no bleeding‐related events in patients with SCD. The mean concentration–time profiles of Pras‐AM were comparable between healthy subjects and patients with SCD following a single 10 mg prasugrel dose and following the 12th dose of 7.5 or 5 mg prasugrel. Conclusions Results demonstrate that in response to prasugrel, patients with SCD and healthy subjects have similar degrees of platelet inhibition and exposure to Pras‐AM, and provide a basis for further study of prasugrel in patients with SCD.